Assessment of risk factors affecting mortality in patients with colorectal cancer - Emre, Arif; Akbulut, Sami; Sertkaya, Mehmet; Bitiren, Muharrem; Kale, Ilhami Taner; Bulbuloglu, Ertan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
Introduction : The most important risk factors for colorectal cancer are age, high ASA score, anemia, low albumin, tumor stage, histopathological properties, tumor's relationship with adjacent tissues, positivity of surgical borders and timing of the surgical procedure. Aim : To determine possible risk factors for mortality in patients undergoing colorectal cancer surgery. Material and methods : The medical records of 101 consecutive patients who underwent colorectal cancer surgery at the Department of Surgery, Sutcu Imam University Faculty of Medicine, Kahramanmaras, Turkey between January 2008 and November 2015 were retrospectively reviewed. The patients were divided into two groups: surviving (n = 76) and deceased (n = 25) groups. The groups were compared in terms of several demographic, clinical, biochemical, and histopathological parameters. In addition, risk factors for mortality were analyzed with multivariate analysis. SPSS 22.2, PAST 3, and MedCalc 14 software packages were used for statistical analyses. Results : The surviving and deceased groups significantly differed with respect to age (p = 0.001), hemoglobin (p = 0.001), lymph node positivity (p = 0.009), positive lymph node/total lymph node ratio (p = 0.012), thrombocyte count (p = 0.047), lymphovascular invasion (p = 0.028), urgency of admission (emergency/elective) (p = 0.036), and postoperative carcinoembryonic antigen (CEA) level (p = 0.002). A receiver operating characteristics curve was drawn to determine the cut-off values of various parameters including age (63), hemoglobin (12.8), node positivity (3), positive/total lymph node ratio (0.435) and thrombocyte count (308), with age (p < 0.001), hemoglobin (p < 0.001), node positivity (p = 0.025) and positive/total lymph node ratio (p = 0.024) being significantly different. A multivariate analysis revealed that age (p = 0.049), hemoglobin (p = 0.045), and positive/total lymph node ratio (p = 0.025) were independent risk factors for mortality. Conclusions : This study shows that older age, lower hemoglobin level, and high positive/total lymph node ratio were independent risk factors for mortality among colorectal cancer patients.